Sentimental Values in Tor-Tor Parsiarabu in Tomok Toba Samosir Village - Martozet Martozet; Nurwani Nurwani (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
This study aims to uncover the form of tor-tor Parsiarabu as a cultural form of  Tomok community's tradition in relation to the sentimentality of the wives left by their husbands. Tor-tor Parsiarabu is an idea of the results of the taste, intention, creativity of the Tomok community in Toba Samosir district for generations. Tor-tor Parsiarabu is closely related to Toba Batak people as the owner of culture, and has always been a support for the survival of the Toba Batak culture itself. Sentimentality is a matter of feeling soft and being easily touched. In order to know the sentimentality in Tor-tor Parsiarabu as a form of the transformation of the rats of the rats, sentimental theory according to Cliford Geertz. The research method is conducted using qualitative methods including literature review, observation, interviews, and documentation. The sentimental form of Tor-tor Parsiarabu seen from motion, music, floor patterns. Sentimentality born of emotions is built from individual widows who are placed collectively. The sentiment that is felt in this tortor is fear of risk, despair, and uncertainty in living life.